Interference of electron wave packets in atomic ionization by subcycle sculpted laser pulses - Arbo, Diego (2014)
We present a theoretical analysis of the atomic photoelectron emission spectra produced by a linearly polarized sculpted laser pulse of two colors with frequencies ω and 2ω. The spectrum of the "direct" electrons with intermediate energies prominently features both intracycle and intercycle interferences. We derive a simple analytic expression for this spectral range based on a semiclassical approximation of the time-dependent distorted wave strong-field approximation generalized to strong-field ionization by a two-color pulse. We verify its applicability to approximately represent the intricate interference patterns by comparison with the exact solutions of the time-dependent Schrödinger equation and with the strong-field approximation. We show that the interference patterns can be tuned and its contrast enhanced by the additional "knob" available, the relative phase between the two frequency components. The present results confirm that two-color ionization allows resolving interference structures originating from trajectories launched within a time interval of less than 100 as [X. Xie et al., Phys. Rev. Lett. 108, 193004 (2012)].